Chapter 6 – Fish now or later? Population processes - Santos, Jorge (Septentrio Educational, 2015)
QUESTIONS ASKED • How to describe the life of a cohort? • How long to wait until we fish a cohort? The dilemma: catch now or later? • How to describe the sexual maturation and the recruitment processes in fish? Pop processes Growth Pop processes Mortality Pop processes Maturation